EFFECT OF CYCLING ON CARDIOVASCULAR HEALTH ASSOCIATED WITH AGING PROCESS - Rynda Rynda; Vidya M. Dewi Tanaka; Inaroh Qudsiyah; Ni Ketut Ayu Maharani; Demak Vera Rachelia; Nadia Carolina Notoprawiro; Kenny Augusto; Made Ayu Mirah Wulandari; Indira Vidiari Juhanna (Sport and Fitness Journal, 2022)
ABSTRACTCycling is a healthy exercise that can be enjoyed by people of all ages, from young children to older adults. Cycling have great attention from the health sector because of aiming to increase levels of physical activity. The main pathways between cycling and health under two perspectives generalizable evidence for health effects and specific impact modeling to quantify health impacts in concrete settings. Risks from air pollution can be assumed to be small, with limited evidence for cycling specific mechanisms. Physical activity, particularly cycling, is known to reduce the risk of cardiovascular diseases, slow down aging, and help in reducing weight and even stress. Keywords: cardiovascular, aging, stress, exercise, cycling